ANALYSING THE GENDER GAP IN EDUCATION ATTAINMENT: A SIMPLE FRAMEWORK WITH APPLICATION TO GHANA. (22nd January 2013) - Nguyen, Minh Cong; Wodon, Quentin
Abstract A simple decomposition is provided to analyse the gender gap in educational attainment with an application to Ghana. The decomposition considers six conditional steps required for completing high school, namely starting and completing primary school, starting and completing junior high school, and starting and completing senior high school. Using household surveys parameters are estimated conditionally on having completed the previous step. By estimating the decomposition over time and comparing parameters between groups, we are able to assess whether the gender gap is being reduced over time and where dropping out takes place in the education system for various groups. Copyright © 2013 John Wiley & Sons, Ltd.